2000
DOI: 10.1016/s0920-5861(99)00283-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and numerical simulation of hydrogen/isobutane permeation and separation using MFI-zeolite membrane reactor

Abstract: A composite alumina-MFI-zeolite membrane has been prepared by a pore-plugging method. Transport through this membrane is controlled by molecular size and adsorption properties, as expected for a defect-free zeolite composite layer.Single gas transport was studied for hydrogen and isobutane. In the studied temperature range, (323-723 K) for isobutane and (277-723 K) for hydrogen, transports were activated. Isobutane exhibited a flux maximum at 450 K, whereas hydrogen flux declined with temperature.These differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 42 publications
(85 reference statements)
2
16
0
2
Order By: Relevance
“…Nanocomposite MFI-alumina membranes have shown their potentials in several gas and vapour separations (e.g., xylene isomer separation [25,26] and ammonia recovery [27]), and combined with a catalyst in membrane reactors (e.g., i-butane dehydrogenation [28,29] and xylene isomerization [25]). Besides, this nanocomposite configuration has also been applied to the synthesis of other membrane materials, such as Pd-ceramic [30] and MCM-41 ("LUS")-alumina [31] membranes, these latter showing high membrane quality together with high gas and water permeation performance and high structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposite MFI-alumina membranes have shown their potentials in several gas and vapour separations (e.g., xylene isomer separation [25,26] and ammonia recovery [27]), and combined with a catalyst in membrane reactors (e.g., i-butane dehydrogenation [28,29] and xylene isomerization [25]). Besides, this nanocomposite configuration has also been applied to the synthesis of other membrane materials, such as Pd-ceramic [30] and MCM-41 ("LUS")-alumina [31] membranes, these latter showing high membrane quality together with high gas and water permeation performance and high structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in temperature the coverage decreases, and is counterbalanced by the increase of the diffusion coefficient up to a certain point, leading to a further global decrease in permeance, as observed for all gases previously studied on this type of membrane [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the studies on nanocomposite MFI-alumina membranes reveal a monotonic decrease of flux with the increase of temperature, which can be explained by pure surface diffusion without an additional "activated diffusion" mechanism (Miachon et al, 2007;Ciavarella et al, 2000). The authors attribute the flux increase in film-like zeolite membranes to the reversible opening of intercrystalline pathways upon heating, based on their investigation through a simple geometric model.…”
Section: General Permeation Behaviormentioning
confidence: 99%
“…b. negligible interactions between the molecules passing through silica pores. It was reported that the gas permeations (i.e., He, Ar, H 2 , N 2 , O 2 , CO, and C 2 H 4 ) through amorphous silica membranes show a predominant increasing trend with the increase of temperature (Smart et al, 2012;Miachon et al, 2007;Nishiyama et al, 1997;Ciavarella et al, 2000;Bai et al, 1995), leading to positive activation energy (Table 2). Exceptionally, the permeation of some large-sized gases such as CO 2 often shows a decreasing trend or a maximum with the increase of temperature, i.e., obviously adsorption-based transport.…”
Section: ) Activated Transport Modelmentioning
confidence: 99%